Modulation of melatonin secretion with transcutaneous auricular nerve stimulation - Rozman, Janez (Materiali in tehnologije, 2021)
The main study objective was to test the hypothesis that selective electrical transcutaneous auricular nerve stimulation (tANS) under forenoon daylight conditions induces melatonin secretion in a 64-year-old male patient with angina pectoris, hypercholesterolomy and coronary artery disease, assuming that it has beneficial effects on accompanied insomnia (Regensburg Insomnia Scale (RIS) = 22 points, the total score ranges from 0 to 40). Silicone stimulation plugs, with two platinum stimulating cathodes each, were inserted into the left and right external ears. Afterwards, one-second-long pulse trains of cathodic, biphasic and current regulated stimulating pulses at stimulating charge density Cd of 50.88 µC/cm2 and frequency of 25 Hz, were delivered for 30 min to selected sites at the upper and lower part of the left and right Cymba Conchae (CC), respectively. The common anode was attached to the neck. The time gap between the pulse trains was measured by the patient using a tactile sensor and was about 250 ms. The results showed that selective tANS under forenoon daylight conditions increased melatonin saliva levels in all the trials accomplished in a patient. Precisely, the lowest increase was obtained in trials with lower right (LR) CC, while the highest increase was obtained in upper-right (UR) CC trials.
Keywords: auricular nerve; avrikularni živec; elektrostimilacija; insomnia; melatonin; nespečnost; stimulacija; stimulation